2013
DOI: 10.1177/1533317513481091
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Driven Interventions for Caregivers of Persons With Dementia

Abstract: Caregiving for a person with dementia can lead to physical and psychological morbidity. Technology-driven interventions hold the promise of convenient, low-cost methods of delivering psychosocial interventions. This systematic review examined the efficacy of technology-driven interventions for caregivers of persons with dementia. A search of Ovid Medline, PsychInfo, and EBSCO from 1990 to May 2012 resulted in the identification of 295 articles. After removal of duplicates, 271 articles were reviewed, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(147 citation statements)
references
References 27 publications
6
140
0
1
Order By: Relevance
“…Narrative syntheses showed positive intervention effects for anxiety in Godwin et al 22 focusing on the Caregiver's Friend and REACH interventions (number of studies unclear, no quality reported); and McKechnie et al 28 after computer-mediated interventions (two studies of high quality). Quantitative syntheses showed statistically significant positive intervention effects for anxiety in Vernooij-Dassen et al 31 following cognitive reframing interventions (four studies, all of which had some methodological limitations).…”
Section: Anxietymentioning
confidence: 99%
See 4 more Smart Citations
“…Narrative syntheses showed positive intervention effects for anxiety in Godwin et al 22 focusing on the Caregiver's Friend and REACH interventions (number of studies unclear, no quality reported); and McKechnie et al 28 after computer-mediated interventions (two studies of high quality). Quantitative syntheses showed statistically significant positive intervention effects for anxiety in Vernooij-Dassen et al 31 following cognitive reframing interventions (four studies, all of which had some methodological limitations).…”
Section: Anxietymentioning
confidence: 99%
“…Similarly, in Macleod et al, 45 risk of bias was reported to have been assessed, but the results of this were not presented. Two reviews 22,34 did not perform any quality assessment of primary studies.…”
Section: Quality Of the Primary Studiesmentioning
confidence: 99%
See 3 more Smart Citations